Thymic Output and CD4 T-Cell Reconstitution in HIV-Infected Children on Early and Interrupted Antiretroviral Treatment: Evidence from the Children with HIV Early Antiretroviral Therapy Trial - Lewis, Joanna; Payne, Helen; Walker, A. Sarah; Otwombe, Kennedy; Gibb, Diana M.; Babiker, Abdel G.; Panchia, Ravindre; Cotton, Mark F.; Violari, Avy; Klein, Nigel; Callard, Robin E. (Frontiers in Immunology, 2017)
Objectives: Early treatment of HIV-infected children and adults is important for optimal immune reconstitution. Infants’ immune systems are more plastic and dynamic than older children’s or adults’, and deserve particular attention. This study aimed to understand the response of the HIV-infected infant immune system to early antiretroviral therapy (ART) and planned ART interruption and re-start. Design: We used linear and nonlinear regression and mixed-effects models to describe children’s CD4 trajectories and to identify predictors of CD4 count during early and interrupted ART. Methods: Data from HIV-infected children enrolled CHER trial, starting ART aged between 6 and 12 weeks, was used to explore the effect of ART on immune reconstitution. Results: Early treatment arrested the decline in CD4 count but did not fully restore it to the levels observed in HIV-uninfected children. Treatment interruption at 40 or 96 weeks resulted in a rapid decline in CD4 T-cells, which on retreatment returned to levels observed before interruption. Naïve CD4 T-cell count was an important determinant of overall CD4 levels. A strong correlation was observed between thymic output and the stable CD4 count both before and after treatment interruption. Conclusions: Early identification and treatment of HIV-infected infants is important to stabilize CD4 counts at the highest levels possible. Once stabilized, children’s CD4 counts appear resilient, with good potential for recovery following treatment interruption. The naïve T-cell pool and thymic production of naive cells are key determinants of children’s CD4 levels.